Influence of the structurization of water on the pressure of its saturated vapor and on the surface tension - Kushnir, S.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
On the basis of the assumption that homogeneously structured liquids have a permanent energy of activation, two functions are constructed for the pressure of saturated vapors (3√P=f(T)) and for the surface tension of water (<span data-mathml="<msqrt>σ</msqrt>=f(T)">√ σ =f(T)) that can keep straightforwardness under the thermobaric conditions of existence of the corresponding structures. Calculations have showed that the first function well describes 4-phase changes of a water structure at the heating, and it is suitable for the analysis of the structurization in other liquids. The second function confirms the homogeneity of structures of the interface in waters of I and II types and the absence of a surface structurization in waters of III and IV types.